Intravenous versus oral paracetamol for acute pain in adults in the emergency department setting: a prospective, double-blind, double-dummy, randomised controlled trial. Issue 3 (15th December 2017) - Furyk, Jeremy; Levas, Deahnne; Close, Benjamin; Laspina, Kathryn; Fitzpatrick, Meghan; Robinson, Kelvin; Vangaveti, Venkat N; Ray, Robin
Abstract : Objective: To determine if intravenous paracetamol was superior to oral paracetamol as an adjunct to opioids in the management of moderate to severe pain in the ED setting. Methods: A prospective, randomised, double-blind, double-dummy, controlled trial was conducted at a single academic tertiary care ED. Adult patients with moderate to severe pain were randomly assigned to receive either the intravenous paracetamol or oral paracetamol. The primary outcome was Visual Analogue Scale (VAS) pain reduction at 30 min. A clinically significant change in pain was defined as 13 mm. Results: 87 participants were included in the final analysis, with a median age of 43.5 years and 59.8% were female. Overall mean baseline VAS pain score was 67.9 mm (±16.0). Both formulations achieved a clinically significant mean pain score reduction at 30 min, with no significant difference between the groups with 16.0 mm (SD 19.1 mm) in the intravenous group and 14.6 mm (SD 26.4) in the oral group; difference −1.4 mm (95% CI −11.6 to 8.8, P=0.79). Secondary outcomes, including postintervention intravenous opioid administration, patient satisfaction, side effects and length of stay, did not differ between groups. Conclusions: Overall, there was a small but clinically significant decrease in pain in each group. No superiority was demonstrated in this trial with intravenous paracetamol compared with oral paracetamol in terms of efficacy of analgesia and no difference in length of stay, patient satisfaction, need for rescue analgesia or side effects.